CORRUPTION WARNING EFFORTS THROUGH EDUCATION AN IDIOLOGICAL APPROACH IN THE FRAMEWORK FULFILLING RIGHTS TO STATE RIGHTS - Dr. Adi Mansar, SH., M. Hum; Dony Hendra Lubis,S.H.,M.H; Ruben Sandi Yoga Utama Panggabean SH , MH; Nicholas Sutrisman,S.H.,M.H (Journal of Islamic, Social, Economics and Development, 2023)
Education is strategically placed to ensure the protection of the nation's and state's life. As a result, any effort or action that undermines the state's integrity, such as terrorism, narcotics and psychotropics, corruption, and human trafficking, must be vigorously opposed. The integrity of the nation and state is jeopardized as a result of systematic and widespread structured corruption ranging from high-ranking officials to village officials. This is proven by the fact that many powerful cabinet ministers have become suspects/defendants (e.g., Idrus Marham). Governors, Regents, and Mayors, civil servants, village leaders, and members of the Senate and Legislature from the Center to the District all happen to be corrupt. In an effort to carry out the prevention and eradication of corruption as mandated in Presidential Regulation Number 55 of 2012 concerning the Long-Term National Strategy for Corruption Prevention and Eradication for 2012-2025 and the Medium Term for 2012-2014 (National Strategy for PPK), preventive and eradication measures have been taken. Every year the Corruption Crime (PPK) is contained in Presidential Instruction Number 2 of 2014 concerning Measures to Prevent and Eradicate Corruption in 2014, attachment to the Inpres section V (five) describes the anti-corruption education and culture strategy which consists of 22 action plans, and involves public and private universities in its implementation.